Cucurbitacin B inhibits HIF-1α and attenuates non-small cell lung cancer via ZFP91 - Song, Lei; Han, Jing; Wang, Run; Cao, Shen; Tai, Yi; Wang, Xinyu; Zheng, Yanjin; Jin, Shufeng; Xing, Yue; Zuo, Hong Xiang; Li, Ming Yue; Ma, Juan; et al. (Frontiers in Oncology, 2025)
Non-small cell lung cancer (NSCLC) is among the most common types of cancer and contributes significantly to cancer-related mortality worldwide. Although some progress has been made in the treatment of NSCLC, drug resistance, high costs, and significant individual variability continue to be major obstacles to effective treatment. Cucurbitacin B (CuB) is a tetracyclic triterpenoid known for its anti-inflammatory and anticancer properties. Previous studies have demonstrated that CuB plays a therapeutic role in NSCLC, however, the mechanism by which it acts necessitates additional research. We used network pharmacology and molecular docking to predict the targets of CuB in NSCLC. Western blot, RT-PCR, immunofluorescence, and co-immunoprecipitation assays were employed to assess the therapeutic effects of CuB on NSCLC in vitro, as well as to elucidate the specific mechanisms involved. Cell colony formation, EDU staining, angiogenesis, scratch assays, and invasion assays, were employed to evaluate the inhibitory effect of CuB on NSCLC. In vivo, C57BL/6 mice were subcutaneously injected with A549 cells to establish lung cancer xenograft models for evaluating the anticancer effects of CuB. Network pharmacology revealed that the primary target of CuB for NSCLC is HIF-1α. Molecular docking studies demonstrated that CuB exhibits strong binding affinity to both HIF-1α and ZFP91. In vitro experiments demonstrated that CuB inhibited HIF-1α expression via ZFP91. Additionally, CuB also suppressed HIF-1α through the Akt/mTOR/p70S6K signaling pathways. Further studies demonstrated that CuB inhibited cell proliferation, migration, invasion, and angiogenesis. In vivo animal experiments have further demonstrated that CuB exhibits a significant therapeutic effect on lung cancer models in mice. Our experiments demonstrated for the first time that CuB inhibits HIF-1α expression through ZFP91. This inhibition reduces the proliferation, migration, invasion, and angiogenesis of lung cancer cells associated with HIF-1α. Additionally, CuB regulates HIF-1α expression by inhibiting the Akt/mTOR/p70S6K signaling pathway. Our findings further elucidate the mechanism by which CuB acts in the treatment of lung cancer, providing a rationale for its development as a therapeutic option for NSCLC.